Opportunity 08 independent ideas for America's next president - O'Hanlon, Michael E. (Brookings Institution Press, 2007)
"Discussion and solutions to pressing policy challenges are presented to help presidential candidates, political observers, and the informed public focus on critical issues facing the nation leading up to the 2008 elections. Tackles a broad range of issues, organized under three categories: Our World, Our Society, and Our Prosperity"--Provided by publisher.